First description of sound emission of Rhaphiptera affinis Thomson, 1868 (Cerambycidae: Lamiinae: Pteropliini) - Hepp, Fábio; Bezerra, Andressa M.; Botero, Juan P. (Zootaxa, 2019)
Cerambycidae is one of the largest families of beetles, containing about 38,000 described species (Tavakilian & Chevillotte 2018). In most species of this family, adults possess a stridulatory device that allows them to produce squeaking sounds (Wang 2017). In the subfamilies Prioninae and Parandrinae, individuals stridulate by rubbing their ridged hind femora against elytral margins (Švácha & Lawrence 2014). In the other subfamilies, including Lamiinae, the stridulation is produced by friction between the ventral face of the posterior pronotal margin (plectrum) and a striated plate on the mesoscutum (pars stridens) (Švácha & Lawrence 2014). Although some adults produce sounds during courtship and copulation, this sound production occurs mainly when individuals are disturbed, being considered a defensive mechanism that might act as a startle response against predators (Dumortier 1963; Švácha & Lawrence 2014; Wang 2017).